2019
DOI: 10.1097/ogx.0000000000000635
|View full text |Cite
|
Sign up to set email alerts
|

Tocolysis: A Review of the Literature

Abstract: Importance Preterm delivery represents an important cause of infant morbidity and mortality. Various tocolytics have been studied with the objective of stopping preterm labor, increasing gestational age at delivery, and preventing complications related to preterm birth. Objective This review aims to summarize the major classes of tocolytics and review the evidence regarding use of each. Evidence Acquisition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
0
16
0
6
Order By: Relevance
“…Expert reviews for preterm labor and birth are identified for the evidenced-based counseling/informed consent content [78][79][80][81][82][83].…”
Section: Maternal/fetal Risk and Complicationsmentioning
confidence: 99%
“…Expert reviews for preterm labor and birth are identified for the evidenced-based counseling/informed consent content [78][79][80][81][82][83].…”
Section: Maternal/fetal Risk and Complicationsmentioning
confidence: 99%
“…The study stated, nifedipine showed to have fewer maternal adverse effects than other analgesics. A recent network analysis and another decision study showed that ca channel blockers would be the best choice antipyretic as far as preterm labour is concerned [15]. It is given orally.…”
Section: [2] Ca Channel Blockersmentioning
confidence: 99%
“…The prevention of PTB remains a great challenge for obstetricians since no causal therapy has yet been established due to its multifactorial etiology (2). The leading symptom of PTB are spontaneous premature uterine contractions, which can effectively be inhibited by tocolytic agents, thus increasing gestational age at delivery (3). However, there is insufficient evidence, that tocolytics significantly reduce neonatal mortality and morbidity (4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is insufficient evidence, that tocolytics significantly reduce neonatal mortality and morbidity (4)(5)(6)(7)(8)(9)(10)(11). The primary objectives of tocolysis are to prolong pregnancy by at least 48 hours to complete fetal lung maturation by application of antenatal corticosteroids (ACS) and to ensure in-utero transfer of the pregnant woman to a perinatal center before 34 weeks of gestation (3,(12)(13)(14). Both are evidence-based measures to improve neonatal mortality and morbidity (11,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation